Identifying people with dementia for epidemiological analysis in electronic primary care records in the UK - Kang, Sujin (2018)
There are many epidemiological questions that need to be answered regarding dementia, including the causes, prognosis, comorbidities, and treatment of the condition and complications. Routine data sources including a large electronic primary care dataset provide a way of investigating some of the complicated factors with rich information. However, there has been concern regarding whether dementia is recorded well enough. It has been reported that dementia is often poorly recorded in primary care and so it would be expected to be potentially difficult to identify people with dementia. Before the data sources can be used satisfactorily, it will be important to understand how dementia is recorded, and whether the records on dementia, related symptoms or use of related medications are the most appropriate ways of identifying people with dementia.